The hidden beginnings of a breakthrough Lina Bo Bardi's first steps in Brazil - Pisani, Daniele 1974- (2022)
Italian-born architect Lina Bo Bardi always claimed that she had moved to Brazil in the aftermath of World War II because the freedom ideals of the Italian Resistance had been betrayed. Recent studies argue she was merely accompanying her husband, Pietro Maria Bardi, who was organizing art exhibitions in Rio de Janeiro. However, as documented by the correspondence published here for the first time, Bo Bardi did not embark on the journey to the New World because of the failures of the Italian Resistance or simply as a companion to her husband: she had been charged with the task of ensuring Brazil’s participation in the eighth edition of the Triennale di Milano (1947). On the basis of the correspondence documenting this assignment, this essay fills a historiographic gap and, more importantly, aims to radically revise the narrative around the initial phase of Bo Bardi’s stay in Brazil, the country she increasingly felt as her own and where she eventually spent her entire life.